2019
DOI: 10.1186/s12889-019-8105-2
|View full text |Cite
|
Sign up to set email alerts
|

The impact of data quality and source data verification on epidemiologic inference: a practical application using HIV observational data

Abstract: BackgroundData audits are often evaluated soon after completion, even though the identification of systematic issues may lead to additional data quality improvements in the future. In this study, we assess the impact of the entire data audit process on subsequent statistical analyses.MethodsWe conducted on-site audits of datasets from nine international HIV care sites. Error rates were quantified for key demographic and clinical variables among a subset of records randomly selected for auditing. Based on audit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0
2

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
3
1

Relationship

4
5

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 21 publications
0
24
0
2
Order By: Relevance
“…Though generally we can hope that errors in EHR data yield estimates with minimal bias, we cannot know this will be the case until we actually validate the study data and examine the quality of the error-prone EHR and directly calculate its impact on estimates. The impact that poor data quality can have on study estimates has been observed time and again to be potentially substantial [18,21,20]. Hence, the size and choice of the validation sample and the analysis methods are critical and can greatly impact precision.…”
Section: Discussionmentioning
confidence: 99%
“…Though generally we can hope that errors in EHR data yield estimates with minimal bias, we cannot know this will be the case until we actually validate the study data and examine the quality of the error-prone EHR and directly calculate its impact on estimates. The impact that poor data quality can have on study estimates has been observed time and again to be potentially substantial [18,21,20]. Hence, the size and choice of the validation sample and the analysis methods are critical and can greatly impact precision.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the standardized definitions and procedures, other studies have emphasized the importance of leveraging local capacity with central technical support, similar to the model of the GN [ 14 , 15 ]. Additionally, as with the GN, the use of ongoing data metrics in routine monitoring reports have been shown to improve data quality [ 5 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Verifying key data elements against source documents through audits improved the quality of the research databases [ 14 ]. Another HIV study [ 15 ] found a discrepancy rate of 17% between pre- and post-audit data of 250 participants, and then investigated the effect of the poor data quality on epidemiologic inference. In 2020, Guidelines for Data Acquisition, Quality and Curation for Observational Research Designs (DAQCORD) were published [ 16 ].…”
Section: Introductionmentioning
confidence: 99%